Development of karst phenomena for geotourism in the Moravian Karst (Czech Republic) - Migoń, Piotr (Geotourism/Geoturystyka)
The Moravian Karst in the south-eastern part of the Czech Republic has considerable potential for the development of geotourism. It is characterized by outstanding geodiversity, revealed in abundant, surface and subterranean karst landforms, as well as protracted history of karst evolution which can be traced back to the Mesozoic. An additional value is provided by the presence of cultural heritage, related to exploitation and processing of mineral resources genetically linked to the karst environment. The significance of this area is further enhanced by easy access to karst landforms and phenomena. Five caves, each of different morphology, can be visited. A dense network of educational trails, marked paths, forestry and field-access roads allows the visitor to reach all interesting features of karst morphology.